Sodium Tanshinone II-A Sulfonate (DS-201) Induces Vasorelaxation of Rat Mesenteric Arteries via Inhibition of L-Type Ca2+ Channel - Zhang, Xiao-Dong; He, Chun-Xia; Cheng, Jun; Wen, Jing; Li, Peng-Yun; Wang, Na; Li, Guang; Zeng, Xiao-Rong; Cao, Ji-Min; Yang, Yan (Frontiers in Pharmacology, 2018)
Abstract Background: We previously have proved that sodium tanshinone II-A sulfonate (DS-201), a derivative of traditional Chinese medicinal herb Danshen (Salvia miltiorrhiza), is an opener and vasodilator of BKCa channel in the vascular smooth muscle cells (VSMCs). Vascular tension is closely associated with Ca2+ dynamics and activation of BKCa channel may not be the sole mechanism for the relaxation of the vascular tension by DS-201. Therefore, we hypothesized that the vasorelaxing effect of DS-20 may be also related to Ca2+ channel and cytoplasmic Ca2+ level in the VSMCs. Methods: Arterial tension was measured by Danish Myo Technology (DMT) myograph system in the mesentery vessels of rats, intracellular Ca2+ level by fluorescence imaging system in the VSMCs of rats, and L-type Ca2+ current by patch clamp technique in Ca2+ channels transfected human embryonic kidney 293 (HEK-293) cells. Results: DS-201 relaxed the endothelium-denuded artery rings pre-constricted with PE or high K+ and the vasorelaxation was reversible. Blockade of K+ channel did not totally block the effect of DS-201 on vasorelaxation. DS-201 suppressed [Ca2+]i transient induced by high K+ in a concentration-dependent manner in the VSMCs, including the amplitude of Ca2+ transient, the time for Ca2+ transient reaching to the [Ca2+]i peak and the time to remove Ca2+ from the cytoplasm. DS-201 inhibited L-type Ca2+ channel with an EC50 of 59.5 M and at about 40% efficacy of inhibition. However, DS-201did not significantly affect the kinetics of Ca2+ channel. The effect of DS-201 on L-type Ca2+ channel was rate-independent. Conclusion: The effect of DS-201 on vasorelaxation was not only via activating BKCa channel, but also blocking Ca2+ channel and inhibiting Ca2+ influx in the VSMCs of rats. The results favor the use of DS-201 and Danshen in the treatment of cardiovascular diseases clinically.